2003
DOI: 10.2223/jped.1051
|View full text |Cite
|
Sign up to set email alerts
|

Pacifier use and its relationship with early weaning in infants born at a Child-Friendly Hospital

Abstract: Objetivo: verificar a prática do uso de chupetas e sua relação com o desmame precoce em crianças nascidas em um Hospital Amigo da Criança.Método: estudo de coorte, longitudinal, envolvendo 250 bebês sadios nascidos no Hospital de Clínicas de Porto Alegre, com peso de nascimento >2.500 g, não gemelares, com o aleitamento materno iniciado, de famílias residentes em Porto Alegre. Os dados foram obtidos mediante entrevista com as mães na maternidade e nas suas casas, no final do primeiro e do sexto mês do bebê e, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
2
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 9 publications
4
9
2
5
Order By: Relevance
“…In contrast with the age of mothers, the results of studies examining pacifier use all agree that using a pacifier is a factor that decreases exclusive breastfeeding duration (22–25). Our study further confirms the already well‐established association between pacifiers and reduced exclusive breastfeeding duration (24,26,27), although the mechanisms involved in this association have not yet been completely explained.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast with the age of mothers, the results of studies examining pacifier use all agree that using a pacifier is a factor that decreases exclusive breastfeeding duration (22–25). Our study further confirms the already well‐established association between pacifiers and reduced exclusive breastfeeding duration (24,26,27), although the mechanisms involved in this association have not yet been completely explained.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast with the age of mothers, the results of studies examining pacifier use all agree that using a pacifier is a factor that decreases exclusive breastfeeding duration (22–25). Our study further confirms the already well‐established association between pacifiers and reduced exclusive breastfeeding duration (24,26,27), although the mechanisms involved in this association have not yet been completely explained. It is possible that using a pacifier reduces the number of breastfeeds per day, resulting in less stimulation of the breast and, consequently, reduced milk production and the need for supplementation (23,27–29).…”
Section: Discussionsupporting
confidence: 85%
“…This was the first time that low maternal education was identified as a protective factor against pacifier use, in contrast with previous studies [34][35][36][37][38][39] . This discrepancy may reflect two peculiarities of the population assessed, namely: (1) all mothers were health professionals; and (2) all had completed at least secondary education (>8 years of formal education).…”
Section: Discussioncontrasting
confidence: 67%
“…If this practice is begun before breastfeeding is established it can lead to weaning, both because of nipple confusion and also because the lack of stimulus leads to a reduction in milk production. Pacifiers were generally given during infants' first month of life and particularly during the first week of life, which has also been observed in other studies (14,21) . Howard et al (22) observed that pacifier use was correlated both with exclusive breastfeeding duration and with breastfeeding duration.…”
Section: Intended To Use a Pacifier (N=390)supporting
confidence: 66%
“…Many authors have suggested that there is an association between pacifier use and reduced breastfeeding duration (13,14) , but the cause-effect relationship is not yet consensus. Children using pacifiers were 22% less likely to be breastfed than children who did not.…”
Section: Discussionmentioning
confidence: 99%